P878 Are cariogenic bacteria the major risk factor for dental caries in patients with ulcerative colitis?. (16th January 2018) - Rodrigues, E; Laranjeira, N; Nunes, G; Barosa, R; Patita, M; Roque Ramos, L; Vieira, A; Fonseca, J
Abstract: Background: Previous reports demonstrated a higher prevalence of dental caries in patients with ulcerative colitis (UC). The risk has been attributed to diet and changes in salivary environment. We aimed to characterise the prevalence of dental caries, salivary flow rates, salivary buffering capacity and cariogenic bacteria counts of Mutans streptococci (MS) and Lactobacillus spp. (LB) in UC patients and evaluate the association between these features, disease activity and duration, and drug therapy. Methods: Cross-sectional study of UC patients followed in a tertiary inflammatory bowel disease clinic. All participants were submitted to a questionnaire, which included demographic data, oral hygiene practice and eating habits and a clinical observation with the assessment of the plaque index and decayed, missing and filled teeth (DMFT) index. Unstimulated and stimulated saliva were collected. Medical records, disease activity (Partial Mayo Score) and duration were also collected. Laboratory data included salivary flow rates, salivary buffering capacity (CRT® buffer) and cariogenic bacteria count (MS and LB) in saliva using the CRT® bacteria test (results: high or low counts). Results: Thirty UC patients were recruited. The most common oral hygiene routines were teeth brushing once or more times a day (96.7%) and the use of fluoride toothpaste (73.3%). DMFT index (mean 16.17 ± 6.428)was not affected by the frequency of soft drinks, cakes, sweets and sugars between meals ( p > 0.2).Patients with long-term disease showed a trend towards higher prevalence of dental caries ( p = 0.06). Most patients presented normal salivary flow rates, both of unstimulated (73.3%) and stimulated saliva (60.0%), as well as high salivary buffering capacity (66.7%). No association was found among these features and age, gender, disease activity and duration or drug therapy. High MS and low LB count were observed in 73.3% and 60% of patients, respectively. Patients with active (100%) and longer duration of disease (88.9%) had higher MS count. Conclusions: Higher prevalence of dental caries was observed in UC patients when compared with general Portuguese data, even though eating habits of UC patients were similar to the general Portuguese population. High MS count was the major risk factor for dental caries and it is probably part of the well-known UC dysbiosis.